TINGKAT KEPERCAYAAN DIRI MAHASISWA PENJAS SETELAH MENGIKUTI PERKULIAHAN SENAM LANTAI - Mulyono, Aji; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The problem in this study was whether there was an increase in self-confidence in physical education students after taking part in floor gymnastics lectures. The purpose of this study was to determine the level of self-confidence of physical education students after taking part in floor gymnastics lectures. The method used in this study was descriptive quantitative survey form, the data used are questionnaires or questionnaires. The sample in this study were the basic education students of FKIP UNTAN in the first semester of the 2018/2019 academic year. Namely, there were 60 students. Based on the calculation of the percentage of the level of confidence of the penjas students after attending the gymnastic floor lectures are as follows: for internal factors, very high (30%), high (66.67%), moderate (3.33%), low (0%) , very low (0%), while external factors are very high (21.67%), high (78.33%), moderate (0%), low (0%), very low (0%). So it can be concluded that the level of self-confidence of short-term students after taking part in a larger gymnastic lecture comes from internal factors compared to external factors. Keyword: Confidence , Lecture , Floor Gymnastics